Cognitive and biologically cryptographic protocols for data security. (August 2019) - Ogiela, Lidia; Ogiela, Urszula
Abstract: This article presents new methods of cognitive computational paragigms dedicated to data security solutions. Especially, these paragidms will be presented based on new, combined classes of threshold schemes – names linguistic-biometric threshold schemes. Linguistic, biometric and combined classes of protocols applied cognitive techniques for data analysis, so new classes of cryptographic threshold schemes also based on cognitive techniques. Cognitive and bilogically cryptographic protocols can be applied for data/secret security. It's possible by used cryptographic techniques based on threshold protocols. These protocols provide secret protection by splitting and distributing shadows between protocol participants. Participants of the protocol receive shadows of a shared secret and ensure their total security by managing them. The authors of this paper have solved the problem of combining existing linguistic and biometric protocols of data protection. The proposed innovative combination of secret protection protocols give new possibilities of application for linguistic-biometric threshold schemes. One of possible application of such protocols is Cloud application, so in this paper will be also describe this possible application. The fundamental methods of data and service protection, dedicated to processes of its security will be describe by cryptographic algorithms, particularly data sharing protocols. This paper will discuss a detailed description of proposed algorithms and their characteristic features.